Pemanfaatan Limbah Ternak Menjadi Pupuk Organik untuk Mendukung Pertanian Berkelanjutan pada Kelompok Tani Mojomakmur, Kota Batu - Mohammad Mahmudi; Muhammad Musa; Evellin Dewi Lusiana; Nanik Retno Buwono; Rakhel Marsyanda Vanny Alvionita; Iren Ana Tasya (Abdi Geomedisains, 2025)
The Mojomakmur farmer group in Mojorejo Village, Junrejo District, Batu City faces the challenge of abundant goat livestock waste that has not been properly utilized, resulting in unpleasant odors and potential environmental pollution. In fact, this waste has high agronomic value when processed into organic fertilizer to support sustainable agriculture. Limited knowledge, skills, and facilities are the main obstacles hindering effective waste utilization. To address these issues, this community service program was carried out through awareness activities on the importance of livestock-waste management, training on the production of solid and liquid organic fertilizers, and the implementation of appropriate technology that farmers can apply easily and efficiently. In addition, intensive mentoring and continuous evaluation were conducted to ensure that the acquired skills can be independently implemented. This program is expected to promote more environmentally friendly waste management, increase the added value of livestock waste for farmers, and strengthen sustainable agricultural practices.